Predictive biomarkers of preeclampsia severity in a low resource setting: Role of red blood cell indices, NLR, and albumin-to-creatinine ratio - Tobing, Immanuel DL.; Lumbanraja, Sarma N.; Lintang, Letta S.; Edwar, Rafli R.; Adenin, Ichwanul; Lubis, Muara P.; Sukatendel, Khairani; Suarthana, Eva (Narra Sains Indonesia, 2024)
Preeclampsia (PE), a serious medical condition with substantial maternal and perinatal implications, poses a significant challenge, particularly in high-incidence countries like Indonesia. Red blood cell (RBC) indices, neutrophil-to-lymphocyte ratio (NLR), and microalbuminuria (albumin-to-creatinine ratio (ACR)) may signal systemic inflammation and endothelial dysfunction, recently recognized as potential indicators for diagnosing and predicting disease severity. The aim of this study was to analyze RBC indices, NLR, and ACR changes in women with PE and their potential for predicting disease severity. A cross-sectional study was conducted at multi-center hospitals across Medan, Indonesia, from June 2022 to June 2023. The patients were grouped into PE cases with and without severe features. Demographic characteristics and complications were recorded while blood and urine were tested. The Chi-squared test, Fisher's exact test and Mann-Whitney test were used to determine biomarkers associated with severe PE. A total of 208 PE patients were included in the study (104 patients for each PE with and without severe features). Our data indicated that PE patients with severe features had higher red cell distribution width (18.5% vs 13.7%; p<0.001), NLR (5.66% vs 4.1%; p<0.001), and ACR (755.97 mg/dL vs 468.63 mg/dL; p<0.001) compared to those without severe features. In contrast, the platelet count was lower in severe features than those without (21.9 × 106/µL vs 27.0 × 106/µL; p=0.002). This study highlighted that PE patients with severe features predominantly had higher levels of RDW, NLR, and ACR and lower platelet counts compared to those without severe features. Therefore, basic tests such as complete blood count and urinalysis, which are inexpensive and feasible in primary care settings with limited resources, offer hope as valuable diagnostic biomarkers for pregnant women diagnosed with PE in a low resource setting.